Symptomatic Bochdalek Hernia in Pregnancy: A Rare Case Report - Selçuk Yetkinel; Çağhan Pekşen; Remzi Kızıltan (Case Reports in Surgery)
Introduction. Symptomatic Bochdalek hernia in pregnancy is quite rare. To the best of our knowledge, there are a total of 44 cases reported in the literature between 1959 and 2016 (Hernández-Aragon et al., 2015; Koca et al., 2016). Difficulty and delay in diagnosis may lead to life-threatening complications. Case Report. We report a case of Bochdalek hernia during the 30 gestational weeks’ pregnancy in whom pregnancy continued after surgical repair which resulted in term birth. Discussion. Bochdalek hernia is diagnosed with an incidence of 1 in 2200–12500 live births, while symptomatic diaphragm hernia is much less in adults. The actual incidence of diaphragmatic hernias during pregnancy is still unknown. Symptoms may include abdominal distension, recurrent abdominal pain, nausea, vomiting, inability to defecate, dyspnea, and chest pain. The patient with diaphragmatic hernia may be asymptomatic until the late weeks of gestation, as in our case, or herniation may occur during advanced gestational weeks with increased intraabdominal pressure. Conclusion. In conclusion, diagnosis of the diaphragm hernia during pregnancy is very rare. Diagnosis is rarer in symptomatic patients due to its rarity and the duration of diagnosis may, therefore, be delayed. Diaphragm hernia should be kept in mind in symptomatic patients due to its high maternal and fetal mortality rates.